The association between family function and adolescents’ non-suicidal self-injury behaviors—is Chinese culture involved? - Yang, Cheng-jia; Zhou, Rui; Liu, Yin-Du; Wang, Shi-Bin; Hou, Cai-Lan; Jia, Fu-Jun (Frontiers in Psychiatry, 2025)
IntroductionNon-suicidal self-injury (NSSI) is prevalent among adolescents with psychiatric disorders and has been closely associated with dysfunctional family environments. In the Chinese cultural context, where family structure and attitudes toward sexuality are unique, the link between family function and adolescent NSSI remains underexplored.MethodsThis cross-sectional study recruited 157 adolescent psychiatric patients (aged 13–18) from both outpatient and inpatient settings. Participants were divided into NSSI and non-NSSI groups based on DSM-5 diagnostic criteria. Family cohesion and adaptability were assessed using the Family Adaptability and Cohesion Evaluation Scales II (FACES II), while clinical and sociodemographic data, including sexual orientation, were collected via structured interviews and standardized instruments.ResultsAdolescents in the NSSI group exhibited significantly lower family cohesion (F = 3.92, p = 0.004) and adaptability (F = 2.95, p = 0.001) than those in the non-NSSI group. Binary logistic regression indicated that lower family function, sexual minority status, and higher depression scores (MARDS) were significant predictors of NSSI. “Unknown” sexual orientation also showed a strong association with NSSI.DiscussionPoor family functioning, particularly in cohesion and adaptability, may increase the risk of NSSI among Chinese adolescents with psychiatric conditions. Additionally, the interplay of Chinese cultural views on family and sexuality may amplify this vulnerability. These findings suggest that family-based interventions and culturally sensitive approaches are critical for the prevention and treatment of NSSI in this population.